Clinical presentation of bluetongue and the malignant form of contagious ecthyma in sheep: Description of cases - Stevanović Oliver; Nedić Drago (Veterinarski Glasnik, 2019)
Bluetongue and contagious ecthyma are sheep diseases that have very similar clinical presentation, thus, making it difficult to distinguish between the two based on clinical symptoms. In practice, a detailed clinical examination of sheep is underestimated and rarely is carried out. The paper presents and describes clinical cases of bluetongue and the malignant form of contagious ecthyma. The differences in the clinical presentation and diagnostic procedures for the two diseases are described in detail, as this information is necessary in order to establish correct disease control measures.